Trabalhadores e trabalhadoras em movimento(s): leigos católicos e outros sujeitos na luta por democracia (ABC Paulista e Grande São Paulo, nas décadas de 1970 e 1980) - Miranda, Vanessa (2020)
This thesis sought to problematize from social psychology records that evidence experiences of participation of the working class in lay movements (Catholic Workers Action, Catholic Workers Youth and Workers Pastoral), popular movements (Basic Ecclesial Communities - CEBs, Cost of Living Movement) , Movement of Defense of the Favelados, Movement of Households) of ABC Paulista and Greater São Paulo against the civil-military dictatorship (1964-1985), which articulated with the struggles of the strike movement (1978-1980) of those regions faced state violence during the period (institutionalization of torture, framed by the National Security Law, the annulment of rights, AI5 (1968), Antigreve Law (1964) and Wage Arrows. The research, carried out in the collection of CPV - Vergueiro Documentation and Research Center and CEDIC - PUC-SP Documentation and Scientific Information Center, sought to analyze a set of Popular Communication materials developed by those movements (mass leaflets, reports, pamphlets, newspapers, drawings, oral testimonies, among others), identifying through the survey of these sources relevant field of study to think about the relations between memory and the historical processes of constitution of the social being in the field of confrontation and creation of struggles for democracy in the decades of 1970 and 1980. The adopted theoretical-methodological framework follows perspectives based on Socio-Historical Psychology, showing, in addition to the documentary and historical value of the analyzed records, that in the process of constituting the social subjectivity of men and women, the organization of those movements began a long journey. towards democratic invention through the path of and the creation of places of struggle and social participation in ABC Paulista and Greater São Paulo, even in times of strong economic, political, cultural and social repression. In this struggle and resistance, spaces that mark the daily life of those working men and women - the church, the factory and the formation of poor and slum neighborhoods - were transformed by organized social movements, altering, at least in those groups, the cultural intertwining of religious practices and the struggles around labor rights against exploitation, contributing to rooting experiences and the formation of spaces for social and community participation in the city. The look launched in this research sought to value the notion of historical subject as an essential potential for the development of public policies, aiming to contribute to the guarantee of human rights based on values that sustained democratic and participatory practices against any state of exception. As a contribution to Social Psychology in Brazil and Latin America, this research also sought to show that the protagonism of the social movements studied here was able to constitute subjective dimensions in the process of creating rights and fighting for democracy